Interpreting Marital Property and Inheritance Rights in Mixed Marriages: A Normative-Transcendental Approach - Hadi, Alpan; Erwin, Yulias; Septyanun, Nurjannah; Jiwantara, Firzhal Arzhi (Law and Economics, 2025)
Intermarriages between Indonesian citizens and foreign nationals are becoming increasingly prevalent in Indonesia's tourist regions, along with the rise of global social and cultural connections. Despite the legal recognition and protection of mixed marriages by Law Number 1 of 1974 regarding Marriage and Law Number 12 of 2006 concerning Citizenship, their execution presents numerous legal challenges, particularly concerning citizenship status, shared property ownership, and inheritance rights. This research employs a normative legal methodology, utilizing literature review as the primary technique, and analyzes Supreme Court Decision No: XXX/Pdt.G/2020/PA.Bdg as a case study. The investigation examined pertinent legal norms, jurisprudence, and relevant legal doctrines by employing a transcendental legal method to comprehend the moral and spiritual principles underpinning these legal frameworks. The study's findings indicate that the national legal system has not adequately addressed the complexities of mixed marriages characterized by divergent legal systems and cultural origins. Restrictions on land ownership by foreign nationals present issues in mixed marriage situations about joint property. Similarly, the disparities in inheritance law systems across civil law, customary law, Islamic law, and foreign frameworks impede equitable arrangements. The transcendental legal approach provides a more inclusive and equitable perspective by grounding legal interpretation in spiritual values. This study advocates for regulatory revisions and the enhancement of international legal frameworks to achieve adaptive and compassionate legal protection that aligns with substantive justice in mixed marriages.